Advanced ADA-GEL bioink for bioprinted artificial cancer models - Bednarzig, Vera; Karakaya, Emine; Leal-Egaña, Aldo; Teßmar, Jörg; Boccaccini, Aldo R.; Detsch, Rainer (Bioprinting, 2021)
One of the main problems encountered in cancer pathologies is the lack of proper in vitro systems resembling the architecture of tumoral tissues. Since 2D surfaces do not represent the morpho-mechanical characteristics of malignant milieus, 3D systems are rapidly gaining interest in the field of Biomaterials for Cancer Research. In this work, we used a new kind of hydrogel-based scaffold constituted by crosslinked alginate di-aldehyde (ADA) and gelatin (GEL) to mimic the tumoral milieu in vitro by biofabrication. For this purpose, flat 2D films and 3D bioprinted scaffolds were crosslinked with solutions of calcium, barium, and combinations of the two. These structures were analyzed in terms of their chemical and mechanical properties, as well as their biological compatibility in the presence of the tumoral cell line HCT116 (colorectal cancer). Our results indicate that ADA-GEL, crosslinked with these divalent ions, can perform effectively as an artificial cancer model, matching the mechanical properties of colorectal tumors, as well as enabling cell growth in confinement. Furthermore, the use of different combinations of divalent ions allowed the tailoring of the mechanical properties of the material. The cell-loaded ADA-GEL constructs are not significantly affected by the type of crosslinking ion. The best outcome was achieved when 3D printed structures were produced with an ADA concentration of 2.5 (w/v)% and crosslinked with barium, showing remarkable results in terms of printability and mechanical properties. With this composition and barium as the crosslinking ion, a stiffness of 44.97 kPa was achieved, compared with calcium crosslinked samples, where it was only possible to achieve an elastic modulus of 21.55 kPa. This work demonstrates that ADA-GEL-based matrices are a very interesting option to perform as tumor-like scaffolds, which could be used to improve current methods of drug testing as well as for personalized medicine.
CRIS-Team Scopus Importer:2021-06-11

Advancing Processing Technologies for Designed Geopolymers: 3D Printing and Mechanical Machining - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Interceram, 2019)
Abstract: Geopolymers continue to attract interest owing to their good mechanical properties in combination with the ecofriendly fabrication process. However, the applications of geopolymers are still restricted to a limited field, mainly as construction materials. Designing and fabricating components of complex, intricate shape for applications beyond building materials may represent a useful approach to broaden geopolymer applications. In this study, unconventional processing and finishing technologies, such as direct ink printing, drilling, and machining are investigated to demonstrate their suitability for geopolymers. Fly ash-based geopolymers incorporating a relevant amount of waste glass demonstrated suitable flow properties to be used in a direct ink printing process. Moreover, the geopolymer specimens showed high machinability: components were drilled and machined in a lathe obtaining superior surface finish, uniform dimensional accuracy, and complex shape parts. The results presented herein indicate opportunities for expanding applications of geopolymers in areas such as mechanical engineering, where components with accurate, specifically designed shapes and surface finish are needed.
CRIS-Team Scopus Importer:2019-08-13

Assessment of in-vitro bioactivity, biodegradability and antibacterial activity of polymer-derived 3D printed åkermanite scaffolds - Dogrul, Fulden; Bednarzig, Vera; Elsayed, Hamada; Liverani, Liliana; Galusek, Dušan; Bernardo, Enrico; Boccaccini, Aldo R. (Open Ceramics, 2023)
Reticulated åkermanite (Ca2MgSi2O7) 3D scaffolds were fabricated by direct ink writing of pastes based on a commercial silicone resin and fillers, such as calcium carbonate (CaCO3) and magnesium hydroxide (Mg(OH)2) microparticles, followed by heat treatment at 1100 °C in air. To form liquid phase upon firing and thus promote the ionic interdiffusion, borax (Na2B4O7·10H2O) or hydrated sodium phosphate (Na2HPO4·12H2O) were considered as alternative additives. Although leading to scaffolds with different strength-to-density ratio, the two additives did not lead to substantial differences in terms of biological response. All fabricated ceramics exhibited acellular in-vitro bioactivity upon immersion in simulated-body-fluid (SBF) as well as antibacterial activity against S. aureus and E. coli. Direct contact cell viability test, performed with a stromal-cell line from mouse bone marrow (ST-2 cells), indicated no cytotoxicity of both samples determined by the WST-8 assay.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Antibacterial activity; Bioactivity; Bioceramic; Cytocompatibility; Direct ink writing (DIW); Polymer-derived-ceramic; Scaffold; Åkermanite

CT-based non-destructive quantification of 3D-printed hydrogel implants - Steinert, Jule; Wittenberg, Thomas; Bednarzig, Vera; Detsch, Rainer; Claussen, Joelle; Gerth, Stefan (Informatik aktuell, 2020)
Additive manufacturing of hydrogel-based implants, as e.g for the human skull are becoming more important as they should allow a modelling of the different natural layers of the skullcap, and support the bone healing process. Nevertheless, the quality, structure and consistency of such 3D-printed hydrogel implants are important for the reliable production, quality assurance and further tests of the implant production. One possibility for non-destructive imaging and quantification of such additive manufactured hydrogels is computed tomography combined with quantitative image analysis. Hence, the goal of this work is the quantitative analysis of the hydrogel-air relationship as well as the automated computation of the hydrogel angles between the different hydrogel layers. This is done by application and evaluation of various classical image analysis methods such as thresholdig, morphological operators, region growing and Fourier transformation of the CT-slices. Results show, that the examined quantities (channels in the hydrogel lattice, angles between the layers) are in the expected ranges, and it can be concluded that the additive manufacturing process may yield usable hydrogel meshes for reconstructive medicine.
CRIS-Team Scopus Importer:2020-04-21

Improved 3D Printing and Cell Biology Characterization of Inorganic-Filler Containing Alginate-Based Composites for Bone Regeneration: Particle Shape and Effective Surface Area Are the Dominant Factors for Printing Performance - Bednarzig, Vera; Schrüfer, Stefan; Schneider, Tom; Schubert, Dirk W.; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2022)
The use of organic–inorganic 3D printed composites with enhanced properties in biomedical applications continues to increase. The present study focuses on the development of 3D printed alginate-based composites incorporating inorganic fillers with different shapes (angular and round), for bone regeneration. Reactive fillers (bioactive glass 13–93 and hydroxyapatite) and non-reactive fillers (inert soda–lime glass) were investigated. Rheological studies and the characterization of various extrusion-based parameters, including material throughput, printability, shape fidelity and filament fusion, were carried out to identify the parameters dominating the printing process. It was shown that the effective surface area of the filler particle has the highest impact on the printing behavior, while the filler reactivity presents a side aspect. Composites with angular particle morpholo-gies showed the same high resolution during the printing process, almost independent from their reactivity, while composites with comparable amounts of round filler particles lacked stackability after printing. Further, it could be shown that a higher effective surface area of the particles can circumvent the need for a higher filler content for obtaining convincing printing results. In addition, it was proven that, by changing the particle shape, the critical filler content for the obtained adequate printability can be altered. Preliminary in vitro biocompatibility investigations were carried out with the bioactive glass containing ink. The 3D printed ink, forming an interconnected porous scaffold, was analyzed regarding its biocompatibility in direct or indirect contact with the pre-osteoblast cell line MC3T3-E1. Both kinds of cell tests showed increased viability and a high rate of proliferation, with complete coverage of the 3D scaffolds’ surface already after 7 d post cell-seeding.
CRIS-Team Scopus Importer:2022-05-06
Keywords: 3D printing; alginate; bioactive glasses; organic–inorganic composites; rheology

Investigation and characterization of the additive manufacturing of polycaprolactone/bioactive glass hybrid scaffolds for bone tissue engineering via material extrusion processing - Gritsch, Lukas; Askanian, Haroutioun; Bednarzig, Vera; Schrüfer, Stefan; Kaschta, Joachim; Blavignac, Christelle; Peuble, Steve; Gallice, Frederic; Jallot, Edouard; Boccaccini, Aldo R.; Lao, Jonathan (Progress in Additive Manufacturing, 2023)
Thanks to its versatility and effectiveness, additive manufacturing is expected to completely revolutionize the biomedical science field. In bone regenerative medicine, in particular, additive manufacturing has the great potential of opening new avenues of development for patient-specific ad hoc therapies. In theory, a defect could be scanned and precisely replicated, thus offering the best fitting for each patient. The main bottleneck to date is the relatively scarce availability of materials that can be printed reliably and consistently. This is the case for organic/inorganic hybrids, materials produced by sol–gel chemistry that combine the advantages of polymers and bioinorganics at the molecular scale. Due to their complex structure and unique rheological and mechanical properties, the printing of hybrids remains challenging. With this study, we aim to investigate the rheological, thermal and molecular properties of a class I polycaprolactone/bioactive glass hybrid and discover how they correlate with the printability of the material. The molecular weight distribution (gel permeation chromatography), thermal properties (thermal gravimetric analysis, differential scanning calorimetry) and rheological properties of each hybrid material were investigated at all stages of processing. Printing trials via direct material extrusion processing followed by morphological characterization were performed on both polymers and hybrids. Their apatite-forming ability in simulated body fluid was evaluated by scanning electron microscopy and particle-induced X-ray emission. Results confirmed the successful manufacturing of organic/inorganic hybrids using direct material extrusion processing for the first time. Three-dimensional scaffolds were successfully produced without the need for further processing. No additional solvents or convoluted indirect approaches were necessary. Thanks to the thermal analysis, an ideal temperature window for printing was identified. SBF immersion assays confirmed that the material's bioactivity is retained after printing. Considering the presented findings, material extrusion processing might develop into an essential technique for fabricating superior 3D bioactive scaffolds for bone tissue engineering. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-09-29
Keywords: Additive manufacturing; Bioactive glasses; Bioactivity; Fused deposition modeling; Hybrids; Polycaprolactone

Rheological examination and 3D bioprinting of pre-gelled alginate hydrogels - Hazur, Jonas; Kaschta, Joachim; Bednarzig, Vera; Boccaccini, Aldo R.; Schubert, Dirk W.; Detsch, Rainer (Nordic Polymer Days 2018, 2018)
lginate hydrogels are from special interest in wound healing, drug delivery and tissue engineering applications, due to their biocompatibility and similarity to the extracellular matrices in tissues [1]. In this project, bioprinting of pre-crosslinked medical grade alginate gels via an internal gelation method using D-(+)-Gluconic acid-lactone in combination with CaCO3 was implemented and the rheological characteristics of the gels were examined. By parameter optimization, it was possible to print 3D porous structures with a height of 5 mm and a pore size of 1.1 mm with those gels. Surprisingly, the stirring process during cross-linking turned out to play a major role for the absolute value of complex viscosity (|η*|), as well as for the homogeneity of the gels. A significant increase of |η*| as well as of the storage modulus was obtained, when the gels were not stirred, leading to gels without viscous flow and therefore to less defined printed structures. Apart from that, the temperature during pre-crosslinking plays an important role on the homogeneity. At lower temperatures than room temperature, the gels showed a more uniform gelation process, compared to those at 20 °C. Furthermore, the concentration and temperature dependence of the alginate solutions were rheologically characterized. The shear dependent viscosities were superposable for both temperature and concentration and appropriate fitting functions in the investigated regions were derive

Self-adhesive resin cements: pH-neutralization, hydrophilicity, and hygroscopic expansion stress - Rödel, Lena; Bednarzig, Vera; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Clinical Oral Investigations, 2016)
The objective of the study was to investigate the relationship between pH-neutralization, hydrophilicity, and free hygroscopic expansion stress of self-adhesive resin cements (SARCs) after storage in artificial saliva.The SARCs RelyX Unicem Automix 2 (RX2, 3 M ESPE), iCEM (iCEM, Heraeus) and Maxcem Elite (MCE, Kerr) were under investigation in this study. Cylinders (height × diameter, 6 × 4mm) were prepared from each material and stored in artificial saliva (7d at 37 °C). Cylinder height was measured at baseline and after 7 days. After storage, the compression modulus was measured to calculate the free hygroscopic expansion stress. For pH-neutralization and hydrophilicity assessment, disks (height × diameter, 1 × 1.5 mm) were prepared, covered with electrolyte, and monitored over 24 h at 37 °C. Hydrophilicity was assessed using the static sessile drop technique at baseline and at different time intervals up to 24 h. Data were analyzed using one-way ANOVA and post hoc Student-Newman-Keuls test (S-N-K, ? = 0.05).After 24 h, RX2 (pH24h 4.68) had a significantly higher (p < 0.05) pH-value than MCE (pH24h 4.2) and iCEM (pH24h 3.23). iCEM showed the significantly highest hydrophilicity (p < 0.05) after 24 h (?24h 85.02°), while MCE resulted lower (?24h 113.01°) in comparison with RX2 (?24h 108.11°). The resulting hygroscopic expansion stress of iCEM (29.15 MPa) was significantly higher (p < 0.05) compared to RX2 (14.5 MPa) and MCE (21.02 MPa).The material with lowest pH-neutralization capacity displayed higher hydrophilicity after 24 h and higher hygroscopic expansion stress after 7 days compared to those with high pH-neutralization.Remnant hydrophilicity due to low pH-neutralization of SARCs could lead to cement interface stress build-up and long-term failure of silicate ceramic restorations.
EVALuna2:24695

The effect of borate bioactive glass on the printability of methylcellulose-manuka honey hydrogels - Schuhladen, Katharina; Bednarzig, Vera; Rembold, Nadine; Boccaccini, Aldo R. (Journal of Materials Research, 2021)
Abstract: 3D printing offers the possibility to generate complex and individualized constructs (scaffolds) for applications in tissue engineering. This is viable by using suitable inks based on advanced biomaterials. Methylcellulose (MC), a highly biocompatible biomaterial, can be combined with manuka honey (H) to fabricate a thermo-sensitive hydrogel. Besides providing favorable biological effects, H can also be used as a natural cross-linking agent. Furthermore, the addition of bioactive glass (BG) to the ink could improve its mechanical and bioactive properties. In this study, a composite based on MC as matrix incorporating H and particulate borate BG as filler, was investigated as ink for 3D printing. Besides the improvement of the inks’ printability owing to the addition of BG, the printed scaffolds exhibited suitable swelling behavior and mechanical properties. Moreover, cell biology tests demonstrated the potential of the composite for biofabrication and applications in tissue engineering, which should be further explored. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-06-18
Keywords: 3D printing; Additive manufacturing; Biomaterial; Porosity

Verarbeitungstechnologien für Geopolymere: 3D-Druck und mechanische Bearbeitung - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Keramische Zeitschrift, 2019)
CRIS-Team Scopus Importer:2019-06-21